2017
DOI: 10.1002/sctm.17-0223
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-1/CD133: Lipid Raft Association, Detergent Resistance, and Immunodetection

Abstract: SummaryThe cell surface antigen prominin‐1 (alias CD133) has gained enormous interest in the past 2 decades and given rise to debates as to its utility as a biological stem and cancer stem cell marker. Important and yet often overlooked knowledge that is pertinent to its physiological function has been generated in other systems given its more general expression beyond primitive cells. This article briefly discusses the importance of particular biochemical features of CD133 with relation to its association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…They were then rinsed and quenched for 10 minutes in PBS containing 50 mM NH 4 Cl prior to the incubation with the appropriate Alexa Fluor 488/546/555‐conjugated goat anti‐mouse IgG 1 (1:500; Molecular Probes, Life Technologies). For the intracellular labeling, PFA‐fixed cells were permeabilized with 0.1% saponin diluted in PBS containing 0.2% gelatin (blocking buffer IV) for 20 minutes at RT prior to immunolabeling for prominin‐1 (see above) and p34‐Arc/ARPC2 subunit of Arp2/3 complex using rabbit antiserum (5 μg/mL; Merck). Primary antibodies were observed using Alexa Fluor 488‐conjugated goat anti‐mouse IgG 1 and Alexa Fluor 555‐conjugated donkey anti‐rabbit IgG.…”
Section: Methodsmentioning
confidence: 99%
“…They were then rinsed and quenched for 10 minutes in PBS containing 50 mM NH 4 Cl prior to the incubation with the appropriate Alexa Fluor 488/546/555‐conjugated goat anti‐mouse IgG 1 (1:500; Molecular Probes, Life Technologies). For the intracellular labeling, PFA‐fixed cells were permeabilized with 0.1% saponin diluted in PBS containing 0.2% gelatin (blocking buffer IV) for 20 minutes at RT prior to immunolabeling for prominin‐1 (see above) and p34‐Arc/ARPC2 subunit of Arp2/3 complex using rabbit antiserum (5 μg/mL; Merck). Primary antibodies were observed using Alexa Fluor 488‐conjugated goat anti‐mouse IgG 1 and Alexa Fluor 555‐conjugated donkey anti‐rabbit IgG.…”
Section: Methodsmentioning
confidence: 99%
“…It is now considered as a stem cell and cancer stem cell marker, although this remains a matter of debate . Association of CD133 with specific lipid rafts is also being debated, and a concept has been proposed whereby “stem cell‐specific lipid rafts” would host determinants necessary for maintaining stem cell properties …”
Section: Exosomes and Differentiationmentioning
confidence: 99%
“…84 Association of CD133 with specific lipid rafts is also being debated, and a concept has been proposed whereby "stem cellspecific lipid rafts" would host determinants necessary for maintaining stem cell properties. 85 Hematopoietic stem and progenitor cells have a self-renewal capacity and can differentiate into mature blood cells. In these cells, it was shown that prominin-1 is present on the cell surface but also in an intracellular pool, partially co-localizing with CD63.…”
Section: Exosomal Release Of Prominin-1 During Cell Differentiationmentioning
confidence: 99%
“…In this respect, immunological synapses formed as interfaces between activated lymphocytes and their cognate antigen presenting cells have been hypothesized to be an example of organized raft domains within the immune system ( 44 46 ). Furthermore, lipid rafts are also discussed to play a crucial role in hematopoietic stem cell homing ( 47 49 ), mobilization ( 47 , 50 , 51 ), and differentiation ( 52 54 ). Moreover, many studies indicate lipid rafts to be involved in various diseases, e.g., HIV-1 infection including a role in virus budding ( 55 , 56 ), cancer ( 57 ), or neurodegenerative disorders such as prion diseases ( 58 ), and Alzheimer's ( 59 , 60 ).…”
Section: The Cell Membrane Is a Highly Complex Lipid Bilayermentioning
confidence: 99%